Electronic structures of CsPb(X x Y1-x)3 perovskites - Nontapat Wanwieng (2020)
© Published under licence by IOP Publishing Ltd. We investigated electronic structures of CsPb(X x Y1-x)3 perovskites, where X, Y = Cl, Br, or I, and x = 0, 1/3, or 2/3, based on the density functional theory (DFT) with generalized gradient approximation (GGA). The results show that these materials exhibit direct and inverted gaps, in the sense that the character of electronic states near the valence band maximum (VBM) is derived from atomic s-like orbital of Pb and p-like orbital of halide atom, whereas the character of states near the conduction band minimum (CBM) is derived from atomic p-like orbital of Pb in contrast with the electronic band structures of other common semiconductors. Their density of states also indicates that the optical transition in both absorption and luminescence are stronger.